REPORTING CLINICAL LABORATORY CRITICAL VALUES: A FOCUS ON THE RECOMMENDATIONS OF THE AMERICAN COLLEGE OF PATHOLOGISTS - AlSadah, Kawthar; El-Masry, Omar S.; Alzahrani, Faisal; Alomar, Amer; Abdel Ghany, Magdy (Journal of Ayub Medical College Abbottabad, 2019)
Background: Reporting critical values continues to receive a widespread attention from health care givers as it symbolizes a crucial clinic-laboratory link. This is because healthcare providers did realize the importance of prompt and timely communication of the critical results, which have positive implications on patient safety and treatment outcomes. In addition to physician and nurses, patients are also recipients of critical values, where they can make informed decisions prior to clinical intervention. The College of American Pathologists (CAP) requires stringent policies for reporting critical values in all laboratories, including adoption of a robust quality assurance system. Research studies have indicated that there still no universally accepted critical values list. This is because of various factors; such as differences in institutional organization, patient population, clinical demand, staffing, and instrumentation. However, through collaboration with other stakeholders involved in the delivery of healthcare, lab professionals may be able to come up with a realistic critical values list that reflects on the local needs and dynamics of patients' service. Conclusion: This review offers an insight into the process of reporting critical values, some challenges encountered, as well as the policies and procedures of effective reporting with a particular focus on the guidelines of the College of American Pathologists. There should be a common global guideline introduced by the health care governing agencies to be adapted with some flexibility in clinical laboratories in different clinical settings. Keywords: Critical values; reporting; guidelines; CAP